2021
DOI: 10.1186/s13075-021-02549-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of anterior uveitis in patients with axial spondyloarthritis treated with anti-TNF or anti-IL17A: a systematic review, a pairwise and network meta-analysis of randomized controlled trials

Abstract: Background Anterior uveitis (AU) is the most frequent extra-articular feature of axial spondyloarthritis (axSpA). We aimed to assess and compare the incidence of AU in axSpA patients treated with anti-TNF or anti-IL17A. Methods We systematically reviewed PubMed, EMBase, and Cochrane from inception to May 3, 2020, and searched for placebo-controlled and head-to-head randomized controlled trials (RCTs) assessing anti-TNF monoclonal antibodies (mAb) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
1
9
1
3
Order By: Relevance
“…The events occurred in 10 patients, of which 9 patients had a history of uveitis. The event and incidence rates of uveitis with upadacitinib were consistent with previous studies with monoclonal tumour necrosis factor inhibitors and interleukin-17 inhibitors 36–38. In the 2-year study, one AE of colitis was reported in a young man without a history of IBD, resulting in an overall IBD event rate of 0.3/100 PY.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The events occurred in 10 patients, of which 9 patients had a history of uveitis. The event and incidence rates of uveitis with upadacitinib were consistent with previous studies with monoclonal tumour necrosis factor inhibitors and interleukin-17 inhibitors 36–38. In the 2-year study, one AE of colitis was reported in a young man without a history of IBD, resulting in an overall IBD event rate of 0.3/100 PY.…”
Section: Discussionsupporting
confidence: 87%
“…The event and incidence rates of uveitis with upadacitinib were consistent with previous studies with monoclonal tumour necrosis factor inhibitors and interleukin-17 inhibitors. [36][37][38] In the 2-year study, one AE of colitis was reported in a young man without a history of IBD, resulting in an overall IBD event rate of 0.3/100 PY. There were no new onsets of IBD among 4 patients who entered the study with a history of IBD at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study contrast those of the NMA published by Roche et al, 11 which reported a decreased incidence of AU with anti‐TNF mAb compared with anti–IL‐17A (odds ratio 0.34, 95% CI 0.12–0.92). There are several likely explanations for why we did not observe similar findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Although Th17 cells have been involved in the induction of inflammation, using an IL-17A blocker to treat patients with inflammatory bowel disease has resulted in disease aggravation (12). Moreover, antibody therapies targeting IL-17A have been ineffective for bowel inflammation or uveitis in AS (13,14), in contrast to the marked effectiveness for psoriasis (15,16). However, emerging data suggest that not all Th17 cells are pathogenic.…”
Section: Introductionmentioning
confidence: 99%